Interpretation of the plants ceonomorphes from the South-East of Ukraine in terms of phyto-indicative scales - A. V. Zhukov (Acta Biologica Sibirica, 2018)
The article shows the discrete nature of the plants ceonomorphes on an example of flora of the southeast of Ukraine. Using discriminant analysis shows that ceonomorphes are discrete classes of plant species which are isolated between themselves to a greater extent than it can be assumed on the basis of only the continuum nature of the ecological differences between species. The predictors used in the discriminant analysis are diapason Didukh’s phytoindicator scales and rescaled Ellenberg scales. The high level of discrimination ability of the model built on the basis of continual predictors shows a considerable species specificity within individual ceonomorphes. The ecomorphic analysis of the ceonomorphes is presented. The aridants as a new ceonomorph is proposed. The reason of the the ceonomorphes compact configuration is a coadaptation of the plant species within each ceonomorphes, as well as in the transforming influence on the environment of the plant community. Using the method of tree classification the rules for the ceonomorphes identification are searched based on the allocation ceonomorphes within phytoindication scales. Phytoindication scales suggested to consider as biotope markers and ceonomorphes suggested to consider as ecotope markers.